Lesser of Two Evils? Slavery in a Comparative Perspective in 19th Century American Travel Narratives of the Ottoman Empire - Pushkin, C. Özge Özmen (Mediterranean Journal of Social Sciences, 2011)
Nineteenth century travels of Americans from various backgrounds to the Ottoman Empire resulted in abundant literaturewhich largely went unnoticed by scholars of American literature in the following centuries. Genre of travel provides the authors withopportunities that are manifold. The most essential of these opportunities were usually the most obvious: representation of self, the youngnation; representation of the other (the Ottoman Empire) and a comparative approach, the result of which would either be reassurance ofthe audience of the superiority of the nation or self-critique. The comparative approach was presented regarding many subjects but one ofthem was not as easily tackled by the authors as the rest: institution of slavery, its practices and repercussions in both lands. This paperpresents a limited survey of this particular comparative approach in nineteenth century American travel narratives by revealing its presenceas well as absence in the authors’ discursive preferences.